Pregabalin versus gabapentin nel trattamento dei pazienti con neuropatia periferica: adattamento di un modello internazionale per la valutazione di costo/efficacia e costo/utilità alla realtà nazionale - Marchettini, Paolo; Da Deppo, Lisa; Pradelli, Lorenzo (Farmeconomia. Health economics and therapeutic pathways, 2005)
OBJECTIVE: To compare the economic impact of treating neuropathic pain with pregabalin versus gabapentin. DESIGN: A cost effectiveness analysis comparing costs and effects of pregabalin 375 mg/die versus gabapentin 1800 mg/die in the perspective of the Italian National Healthcare Service was developed. The cost effectiveness analysis is examined alternatively in terms of the incremental cost per additional day with no or mild pain, and the incremental cost per quality-adjusted life-year (QALY) gained. Effects were derived from a pregabalin randomised clinical study 1008-155 and gabapentin 645-210 and 945-211 studies. Effects are expressed as reduction score of the VAS pain scale. Pharmacological costs were quantified according to the Italian market price of the drugs; healthcare procedure and hospitalisation costs were quantified on the basis of the National Tariff. Other healthcare services consumption data were derived from a Delphi Panel. To estimate the impact of pregabalin and gabapentin on daily pain experience in patients with neuropatic pain a Markov model is used. The dynamic simulation focuses on a hypothetical cohort of 1000 patients and simulates their daily pain experience over 12 weeks, to estimate clinical and economic outcomes for the group as a whole. MAIN OUTCOME MEASURES AND RESULTS: The cost-effectiveness ratio for the use of pregabalin is less than 1 euro per additional day with no or mild pain and 468 euros per QALY. The sensitivity analysis conducted to examine the effects of decreasing gabapentin dose to 1200 mg/die showes the consistency of the model results. CONCLUSIONS AND RESULTS: Although pregabalin pure costs are higher than gabapentin costs, the analyses prove pregabalin to be more effective with a small additional cost per day with no or mild pain.